KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN 006 RANTEBULAHAN KABUPATEN MAMASA - Ardy Abraham; Wahira; Faridah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to outline the principal's instructional leadership strategies for implementing the Merdeka Curriculum at SDN 006 Rantebulahan in Mamasa Regency. The principal's leadership style, motivating and impeding elements, and attempts to overcome implementation obstacles are among the topics covered. This study used a case study design and a qualitative methodology. Documentation, in-depth interviews, and observation were used to gather data. Teachers, administrative staff, and the principal were the research subjects. The Miles and Huberman model, which comprises data reduction, data display, and conclusion drawing, was used to examine the data. According to the findings, the principal is crucial in defining the school's goals and objectives, planning lessons in accordance with the Merdeka Curriculum, enhancing teachers' methods, and creating a supportive learning environment. Parental involvement, instructor zeal, and government policy backing are examples of supporting variables. Limited resources and an early lack of curriculum understanding are among the difficulties faced. Through internal training, teamwork, and the provision of pertinent learning materials, the principal overcame these difficulties.